(untitled) (Journal of Informatics and Mathematical Sciences, 2025)
Civil megastructures, such as skyscrapers, long-span bridges, and large-scale infrastructure projects, represent the pinnacle of engineering innovation, requiring precision, efficiency, and sustainability in their design and construction. The integration of Artificial Intelligence (AI) into civil engineering has revolutionized the design process, enabling unprecedented levels of optimization, safety, and sustainability. This paper explores the multifaceted applications of AI in the design of civil megastructures, including structural analysis, generative design, construction automation, and risk assessment. By leveraging machine learning, deep learning, and other AI-driven methodologies, engineers can address complex challenges, enhance project outcomes, and push the boundaries of modern civil engineering. This comprehensive analysis highlights the transformative potential of AI, offering insights into its current applications, challenges, and future directions in the design of megastructures.